Screening for perfluoroalkyl acids in consumer products, building materials and wastes - Bečanová, Jitka; Melymuk, Lisa; Vojta, Šimon; Komprdová, Klára; Klánová, Jana (Chemosphere, 2016)
Perfluoroalkyl and polyfluoroalkyl substances (PFASs) are a large group of important chemical compounds with unique and useful physico-chemical properties, widely produced and used in many applications. However, due to the toxicity, bioaccumulation and long-range transport potential of certain PFASs, they are of significant concern to scientists and policy makers. To assess human exposure to PFASs, it is necessary to understand the concentrations of these emerging contaminants in our environment, and particularly environments where urban population spend most of their time, i.e. buildings and vehicles. A total of 126 samples of building materials, consumer products, car interior materials and wastes were therefore analyzed for their content of key PFASs - 15 perfluoroalkyl acids (PFAAs). At least one of the target PFAAs was detected in 88% of all samples. The highest concentration of Σ15PFAAs was found in textile materials (77.61 μg kg-1), as expected, since specific PFAAs are known to be used for textile treatment during processing. Surprisingly, PFAAs were also detected in all analyzed composite wood building materials, which were dominated by perfluoroalkyl carboxylic acids with 5-8 carbons in the chain (Σ4PFCAs up to 32.9 μg kg-1). These materials are currently widely used for building refurbishment, and this is the first study to find evidence of the presence of specific PFASs in composite wood materials. Thus, in addition to consumer products treated with PFASs, materials used in the construction of houses, schools and office buildings may also play an important role in human exposure to PFASs.
Keywords: PFASs; Household Articles; Humans; městské obyvatelstvo; Carboxylic Acids; Environmental Monitoring; konstrukční materiály; Indoor; kyseliny karboxylové; lidé; textilie; Waste Products; Construction Materials; látky znečišťující životní prostředí; Building materials; monitorování životního prostředí; Consumer Product Safety; Environmental Pollutants; Textiles; spotřebitelská bezpečnost produktů; potřeby pro domácnost; PFOS; Consumer products; fluorokarbony; odpadní produkty; Fluorocarbons; Urban Population